Afiksasi dan Reduplikasi dalam Bahasa Remaja pada Kolom Komentar di Media Sosial Facebook Bulan Oktober-November Tahun 2023 - Yewi, Delila; Madeamin, Rosmini; Muliana, Hanana (Progressive of Cognitive and Ability, 2024)
Affixation and Reduplication in Youth Language in the Comment Column on Facebook Social Media in 2023. Thesis, Department of Indonesian Language and Literature Education, Faculty of Teacher Training and Education, Muhammadiya University, Makassar. Supervised by Rosmini Madeamin and Hanana Muliana. This research is qualitative research with certain studies or studies using descriptive qualitative procedures which aim to describe forms of affixation and reduplication in adolescent language in the comments column on Facebook social media in 2023. The subject of this research is Facebook social media by collecting data through observation, documentation, reading. and note it down. The results achieved after analyzing the data on affixation based on the data obtained were that there were three types of prefixes, namely (nge-, ng-, ny-). -in) and data in infixes (-er-, -em-, -el-). Data analysis on reduplication, based on the results obtained, there are four types of reduplication, namely complete, partial, pseudo and sound-changing reduplication.